PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI INFORMASI, DAN SISTEM PENGENDALIAN INTERN TERHADAP NILAI INFORMASI PELAPORAN KEUANGAN ENTITAS AKUNTANSI PEMERINTAH DAERAH (Studi Persepsi Pegawai SKPD di Kabupaten Batang dan Kabupaten Kendal) - Rizal Pramudiarta; Agung Juliarto (Diponegoro Journal of Accounting, 2015)
This research is conducted to investigate the factors that affecting the information value of accounting entity financial reporting. The factors under investigation are the human resources competency, information technology, and government internal control system.Data were collected using questionnaire survey. The questionnaires were delivered to 65 employees of local government units (SKPD) Batang Regency and Kendal Regency specifically at financial / accounting department. A total of 65 questionnaires (100%) were returned and can be processed. The data were processed using SPSS version 19.0. The multiple linear regression analysis was employed to test research hypotheses.The results of hypothesis testing show that human resource competency, and the government internal control system have significant positive effects on the information value of accounting entity financial reporting. Whereas the use of information technology has no a possitive effect on the information value of accounting entity financial reporting.